2018
DOI: 10.1038/s41389-018-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of miR-22 modulated by RelA/p65 in resensitizing fulvestrant-resistant breast cancer cells to fulvestrant by targeting FOXP1 and HDAC4 and constitutive acetylation of p53 at Lys382

Abstract: Antiestrogen resistance is a major challenge encountered during the treatment of estrogen receptor alpha positive (ERα+) breast cancer. A better understanding of signaling pathways and downstream transcription factors and their targets may identify key molecules that can overcome antiestrogen resistance in breast cancer. An aberrant expression of miR-22 has been demonstrated in breast cancer; however, its contribution to breast cancer resistance to fulvestrant, an antiestrogen drug, remains unknown. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 64 publications
1
30
0
1
Order By: Relevance
“…Unlike other TET proteins, TET2 does not have a putative DNA-binding domain 6 and can be recruited to specific chromatin regions through interaction with DNA-binding transcription factors 10 , 26 – 28 . To identify key transcription regulatory elements and putative transcription factors that may serve as co-activators of TET2 to mediate gene expression of Foxa1, Gata3 , and Esr1 , we performed promoter analysis (Genomatix MetInspector) and found that Forkhead box protein P1 (FOXP1) binding motif was the most enriched in the promoter regions of all three FOXA1, GATA3, and ESR1 genes (high matrix consensus score greater than 0.99) and might serve as a potential transcription factor to modulate expression of these genes (Supplementary Data 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other TET proteins, TET2 does not have a putative DNA-binding domain 6 and can be recruited to specific chromatin regions through interaction with DNA-binding transcription factors 10 , 26 – 28 . To identify key transcription regulatory elements and putative transcription factors that may serve as co-activators of TET2 to mediate gene expression of Foxa1, Gata3 , and Esr1 , we performed promoter analysis (Genomatix MetInspector) and found that Forkhead box protein P1 (FOXP1) binding motif was the most enriched in the promoter regions of all three FOXA1, GATA3, and ESR1 genes (high matrix consensus score greater than 0.99) and might serve as a potential transcription factor to modulate expression of these genes (Supplementary Data 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that TET2 can be a direct target of the Let-7adf cluster in LPS-activated macrophages 33 , it can be suppressed by miR-29 in prostate cancer cells 9 , and it is down-regulated by miR-22 in breast cancer cells 34 . miR-22, a microRNA that is associated with oncogenic signaling and overexpressed in high-grade breast tumors with poor clinical outcomes 26 , 34 , 35 , directly targets TET family members, including TET2, which in turn leads to hypermethylation of the mir-200 promoter and induction of breast cancer stemness phenotype and metastasis 34 . The associated TET2 regulatory mechanism was further elaborated by another study that showed TET2 could complex with RARβ to epigenetically activate a cohort of gene targets involved in cell differentiation, including RUNX1, BMP6, IKZF1 and CAV1 , and Mir-200c 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival and growth of multiple myeloma is regulated by the HDAC4-RelB-p52 complex, and the disruption of the latter blocks the growth of these cells [ 46 ]. Moreover, HDAC4 degradation by certain chemotherapeutic agents results in the apoptosis of head-and-neck cancer cells that are resistant to TRAIL, while miR-22-driven HDAC4 repression helped to resensitize fulvestrant-resistant breast cancer cells [ 47 , 48 ]. Likewise, eptoposide resistance in human A549 lung cancer cells was conferred by STAT1-HDAC4 upregulation, and HDAC4 inhibition has been reported to induce apoptosis in non-small cell lung cancer PC-9 cells [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both HDAC3 and HDAC6 could increase the expression of survivin and siRNA treatment of HDAC3 and HDAC6 showed a similar effect of SAHA and induced autophagy in MCF7 and MDA-MB-231 cancer cells (Lee et al, 2016). miRNA-22, miRNA-10b and miRNA-125a-5p was suggested to interact with HDAC4 and contributed an impact on the drug-resistance in breast cancer cells (Ahmad et al, 2015;Hsieh et al, 2015a;Wang et al, 2018). Similar to HDAC4, HDAC5 also displays a regulatory effect on tumor resistance in breast cancer, which is related to its regulation of cell proliferation, cell differentiation and autophagy (Hsieh et al, 2015b;Li et al, 2016;Cao et al, 2017;Huang et al, 2017;Cao et al, 2018;Xue et al, 2019).…”
Section: Insight Into the Histone Acetylationmentioning
confidence: 98%